Model Financial Distress: Pengaruh Likuiditas, Leverage dan Pelaporan ESG - Sri Ayem; Ratnawati Bule (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
Financial Financial distress can arise when a company's ability to maintain financial stability weakens and the risk of bankruptcy increases. This research examines liquidity, leverage, and ESG reporting as factors for financial distress. The study focused on food and beverage issuers listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. The sample was selected using a purposive sampling technique, resulting in 25 issuers with 100 annual report data sets. Data testing included descriptive numerical analysis, regression prerequisite checks, and multiple regression models using SPSS. Empirical findings indicate that liquidity, leverage, and ESG reporting have a positive influence on financial distress. These results can be used as considerations by management in managing short-term repayment capacity, the proportion of debt-based funding, and the quality of sustainability information to minimize the likelihood of financial distress.